A multicriteria decision support system for housing evaluation - Natividade-Jesus, Eduardo (2007)
Economic and population growth, higher life quality standards, and lower interest rates have led to an increase in the demand for housing. However, in many urban areas, land for housing is becoming scarce, and environmental and construction requirements more stringent.